189: Parental Knowledge of Concussion. Issue 6 (1st June 2014) - Weerdenberg, K; Schneeweiss, S; Koo, E; Boutis, K
Abstract: BACKGROUND: Since concussions commonly occur during play/sport, parents may have a key role in advocating for sport removal and assessment by a physician. However, information on parental knowledge of recognizing and understanding concussion is currently very limited. OBJECTIVES: We determined how frequently parents knew that a concussion represented brain injury without associated bleeding. We also examined parental awareness of symptoms after head injury that may be related to a concussion, appropriate actions if concussion is suspected, and return-to-play guidelines DESIGN/METHODS: Parents of children five to 18 years of age presenting to a pediatric emergency department within two weeks of a head injury were asked to participate in a 24-item questionnaire. Survey questions were derived and validated using expert opinion, available literature, and pre and pilot testing of questions on the target audience. RESULTS: Of 674 eligible parents, 507 (75.2%) were enrolled. Of these, 342 (67.5%) were female, 411 (81.1%) were 31 to 50 years of age, 435 (85.8%) had post-secondary education, and 77 (15.2%) reported a history of concussion. Importantly, 288 (57.4% [95% CI 53.1% to 61.7%]) parents correctly identified concussion as non-hemorrhagic brain injury, and 414 (82.5%; [95% CI 79.2% to 85.8%]) were aware of short and long-term symptoms after head injury that may be related to concussion. There were no parental demographics that were significantly predictive of concussion knowledge. Of the respondents, 40.0% believed their child's current head injury may be a concussion, while physician diagnosed concussions for this population's was 29.3% (P=0.45). The inter-rater agreement between physicians and parents in labeling the child's head injury as a concussion was poor, kappa = 0.011. If a parent thought their child had a concussion, 460 (91.5%) would appropriately stop the child's play and see a physician. Although 502 (99.0%) understood that a concussion would lead to restricted activities for the child, only 147 (29.0%) were familiar with return-to-play guidelines. CONCLUSIONS: Many parents were aware that a concussion is a type of non-hemorrhagic brain injury. Further, most knew the symptoms after head injury that may be associated with a concussion, and the appropriate actions to take once this injury is suspected. However, an early physician visit is recommended to provide families with an assessment for correct diagnosis and educate families on appropriate anticipatory guidance and follow up for this injury.